New substrate medium mixture can improve the initial growth of Hylocereus costaricensis (Haw) - Oliveira, Luana Mendes; Mendonça, Vander; Moura, Elias Ariel; Melo, Marlenildo Ferreira; Figueiredo, Francisco Romário; Celedônio, Wilma Freitas (Comunicata Scientiae, 2022)
Dragon fruit is an exotic species that has currently shown great relevance in the world market. Hence, the demand for materials with high genetic potential has increased. Genetic propagation allows selecting materials with high yield and climatic conditions adaptation. The selection of the substrate influences the quality of the seedling, which should provide adequate conditions for germination and root development. This study aimed to evaluate the seed emergence and initial growth of dragon fruit cultivated in different substrates under nursery conditions. The experiment was carried out in a completely randomized design, with 11 treatments, four replications, and 25 seeds per replication. The treatments used were composed of the soil, mixture with organic compost and commercial substrate. First emergence count, emergence percentage, and emergence speed were evaluated up to 50 days after sowing. Data of shoot length, stem diameter, root length, shoot dry matter, and root dry matter were recorded at 88 days after emergence. The treatment of washed sand + coconut fiber and Tropstrato® provided a higher emergence percentage and emergence speed of dragon fruit seeds. The treatment of coconut fiber + Tropstrato® + organic compost allowed better means for stem diameter, shoot dry matter, and root dry matter. Conversely, the treatments of washed sand + Tropstrato® and Tropstrato® resulted in greater root system growth.